Togo : Assessment Letter for the World Bank. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This note provides the IMF staff assessment of recent macroeconomic developments in Togo and progress under the Fund-supported three-year Poverty Reduction and Growth Facility program (PRGF) starting from January 2008 based on preliminary information through end-December 2008.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet